2005
DOI: 10.1128/cdli.12.5.632-639.2005
|View full text |Cite
|
Sign up to set email alerts
|

Association of Uterine and Salpingeal Fibrosis with Chlamydial Hsp60 and Hsp10 Antigen-Specific Antibodies inChlamydia-Infected Koalas

Abstract: Infection by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 38 publications
1
34
0
1
Order By: Relevance
“…Transforming growth factor (TGF)-β1 and interleukin (IL)-6 induce Th17 cells, and they start secretion of IL-17A; which acts itself as profibrotic for myofibroblasts and further stimulates inflammatory cells for TGF-β1 secretion (16). Regulatory T cells a have dual function in fibrogenesis; subsets produce TGF-β1 and promote fibrosis, whereas other release immunosuppressive cytokines IL-10 (17).…”
Section: Pathogenesis Of Liver Fibrosismentioning
confidence: 99%
“…Transforming growth factor (TGF)-β1 and interleukin (IL)-6 induce Th17 cells, and they start secretion of IL-17A; which acts itself as profibrotic for myofibroblasts and further stimulates inflammatory cells for TGF-β1 secretion (16). Regulatory T cells a have dual function in fibrogenesis; subsets produce TGF-β1 and promote fibrosis, whereas other release immunosuppressive cytokines IL-10 (17).…”
Section: Pathogenesis Of Liver Fibrosismentioning
confidence: 99%
“…Although cHsp60 clearly plays a prominent role in chlamydial pathogenesis, it is not the only molecule involved. The genetically linked protein cHsp10, encoded by the groES gene upstream of groEL-1, is also associated with disease complications (6,23,27,33). Moreover, several studies have demonstrated that genetic predisposition plays a significant role in chronic chlamydial disease (10,12,38).…”
mentioning
confidence: 99%
“…Patients with coronary artery disease often have serological evidence of previous infection by Chlamydia pneumoniae (45), and cHsp60 has been directly identified in human atheromatous tissue (31). Most recently, C. pneumoniae and Chlamydia pecorum cHsp60s have been implicated in urogenital tract disease in koalas (Phascolarctos cinereus), leading to infertility and death; chlamydiae are the most commonly recognized disease agents in the threatened koala population (23,24).…”
mentioning
confidence: 99%
“…7,10,36 Together, chlamydial infections contribute not only to the overall health decline of koala populations, but also to reduced reproductive rate. 4,12,22 In addition to Chlamydia spp., a number of other bacterial organisms, including Mycoplasma spp. and Ureaplasma 770490V DIXXX10.1177/1040638718770490Multiplex PCR detection of bacterial pathogens in koalasHulse et al spp., may contribute to population decline, but their epidemiology and pathogenicity have yet to be fully characterized in the koala.…”
Section: Introductionmentioning
confidence: 99%